Site response analysis of the city of Surabaya, Indonesia - Cheong, Mun Shee. (2010)
Numerous earthquake events have been witnessed all over the world, especially in the Southeast Asia. It has caused destructions, deaths and most importantly, affected the economy adversely. The magnitude of Earthquake is factored by its source, transmission path and the site effect. In this project, the site effect will be discussed. The investigation is conducted in Surabaya, Indonesia from the period 9th December 2009 to 20th December 2009. The subsurface structure of the ground can be determined either by borehole drilling or carrying out Microtremor Survey method (MSM). Since Surabaya has been heavily populated and the cost of carrying out borehole drilling is more expensive, MSM is hence, adopted in our experiment. The objective of this project is to investigate and determine the depth of the ground layer by the two microtremor survey method, namely, SPAC (Spatial Autocorrelation) method and the F-K (Frequency-Wavelength) method. The purpose is to find out the hardness of soil layer below ground and the way they affect and influence the site when there is ground movement. During the field experiment, large, medium and small triangular were set up at various parts of Surabaya. From the field observation, data will be acquired and process by the two methods. By adjusting the parameters, graphs will be plotted to determine the surface velocity and depth of the subsurface structure. In this report, three locations were covered. They are i) EMB, ii) COM and iii) PAK. The P-waves and S-waves velocity together with the depth of different layers of soil have been determined and discussed. Based on the International Building Code, the site is classified according to the shear velocity into different class of hardness. The result of experiments showed that all three sites has stiff soil profile, however, the range of shear velocity used to determine the site are at the lower end of the profile and are close to being soil soft profile and hence, it can be considered as seismic areas that are of relatively high risk.